2022
DOI: 10.3390/ani12030303
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link between Vomeronasalitis and Aggression in Stable Social Groups of Female Pigs?

Abstract: The vomeronasal organ (VNO) is a bilateral chemosensory structure strongly involved in animal behaviour, thanks to its sensory epithelium (VNSE) that detects pheromones. Experimental VNO lesions can impair social, reproductive and maternal behaviour, while feline spontaneous vomeronasalitis has been associated with aggression. This study aimed to describe vomeronasalitis in farm pigs and explore its association with intraspecific behavioural alterations. Using 38 six-month-old pigs, the skin lesion score based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…This study allowed us to better characterize vomeronasalitis in pigs and the modifications the condition induces in the VNO. Asproni et al ( 21 ) demonstrated that, when inflammation was present in a pig's VNSE, the animal was more susceptible to aggression by congeners. Our results showed that inflamed VNSE possesses a lower number of neurons responsible for chemoreception.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study allowed us to better characterize vomeronasalitis in pigs and the modifications the condition induces in the VNO. Asproni et al ( 21 ) demonstrated that, when inflammation was present in a pig's VNSE, the animal was more susceptible to aggression by congeners. Our results showed that inflamed VNSE possesses a lower number of neurons responsible for chemoreception.…”
Section: Discussionmentioning
confidence: 99%
“…Asproni and colleagues revealed that the presence of VNO spontaneous inflammation (vomeronasalitis) was also associated with intraspecific aggression in cats (20). This link was recently confirmed in a stable social group of pigs, in which a strong correlation was found between the histological scores of VNO inflammation intensity and the number of skin lesions induced by social fighting (21).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations